2009
DOI: 10.1136/adc.2008.143057
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for respiratory syncytial virus hospitalisation in children with heart disease

Abstract: In children with heart disease risk factors for RSV admission are Down syndrome, cardiomyopathy and haemodynamically significant heart disease. Young age and cardiac decompensation are associated with a more severe course of RSV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 36 publications
5
51
0
1
Order By: Relevance
“…Down syndrome (DS) is an independent risk factor for respiratory illness and severe respiratory syncytial virus (RSV)-related infection and hospitalization in children. [1][2][3][4][5][6][7][8] The combined attributes of a compromised innate and adaptive immune system in early infancy [9][10][11][12][13] with anatomic [14][15][16] and physiologic aberrations such as gastroesophageal reflux disease, 17 obstructive sleep apnea, 18 and hemodynamically significant heart disease 4,19 all lead to significant morbidity and mortality in DS during the first 2 years of life. [20][21][22] Palivizumab, a humanized monoclonal antibody, has been proven safe and efficacious against RSV in randomized, placebo-controlled studies involving preterm infants #35 weeks' gestational age during their first RSV season and children aged ,2 years with severe chronic lung disease (CLD) and hemodynamically significant cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Down syndrome (DS) is an independent risk factor for respiratory illness and severe respiratory syncytial virus (RSV)-related infection and hospitalization in children. [1][2][3][4][5][6][7][8] The combined attributes of a compromised innate and adaptive immune system in early infancy [9][10][11][12][13] with anatomic [14][15][16] and physiologic aberrations such as gastroesophageal reflux disease, 17 obstructive sleep apnea, 18 and hemodynamically significant heart disease 4,19 all lead to significant morbidity and mortality in DS during the first 2 years of life. [20][21][22] Palivizumab, a humanized monoclonal antibody, has been proven safe and efficacious against RSV in randomized, placebo-controlled studies involving preterm infants #35 weeks' gestational age during their first RSV season and children aged ,2 years with severe chronic lung disease (CLD) and hemodynamically significant cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Across 4 reported studies, [1][2][3]5 which have cumulatively evaluated 1646 children with DS aged ,2 years, the risk estimate for RSV hospitalizations ranged from 9.9% to a Adjusted for hemodynamically significant CHD, insignificant CHD, gestational age, and birth weight. Ratios .1 indicate higher risk in the untreated group.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying disease, especially chronic lung disease of prematurity and haemodynamically significant congenital heart disease, is a significant predictor of prolonged hospitalisation, frequency of ICU admission and death in children hospitalised for RSV [107,109]. Conditions such as other symptomatic chronic pulmonary disorders, trisomy 21 and neuromuscular disease also increase the risk for severe disease [110][111][112]. Furthermore, a role for genetic predisposition in severe RSV disease is supported by identical twin studies [91] and observed increases in susceptibility of the male gender and specific ethnic or racial groups such as Native American and Canadian Inuit populations [108].…”
Section: Risk Factors For Severe Diseasementioning
confidence: 99%
“…They are also more prone to respiratory tract infections (RTIs) that commonly manifest in the lower airways, a major cause of hospitalization (5,6). Several factors contribute to increased risk of RTI in children with DS such as neurological impairment (7), abnormal anatomy of the upper airways (8), structural pulmonary abnormalities (9), and congenital heart defects (10). In addition, alterations in the immune system are an important cause of RTIs in DS children (11,12).…”
mentioning
confidence: 99%
“…These lower RTIs in DS children are most often caused by viral pathogens, such as respiratory syncytial virus. This can lead to severe respiratory syncytial virus bronchiolitis, a frequent cause of hospitalization in DS children (10,(26)(27)(28). Also, an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection was reported in DS (29).…”
mentioning
confidence: 99%